Method for optimizing roughness of side wall of glass through hole

Through the laser-induced modification and optimization of the use of etching liquid of femtosecond laser, the roughness of the sidewall of the glass through hole is significantly reduced, and the problem of high sidewall roughness in the prior art is solved, and signal transmission efficiency and structural reliability are improved.

CN119581331APending Publication Date: 2025-03-07CHENGDU MAIKE TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411687254.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the existing glass through-hole technology, the through-hole side wall has high roughness, resulting in low signal transmission efficiency, insufficient bonding strength and reduced overall reliability.

Method used

The glass substrate is laser-induced to modify the femtosecond laser to form a prefabricated through-hole modified area, which improves its sensitivity to chemical etching. Prepare an optimized etching solution, including deionized water, hydrofluoric acid, ammonium fluoride, isopropanol and polyethylene glycol, control the etching solution temperature and ultrasonic power to achieve uniform and refined chemical etching.

Benefits of technology

The roughness of the side wall of the glass through holes is significantly reduced, from 1.257 microns to below 100 nanometers, improving signal transmission efficiency and the bonding strength of the through holes and fill materials, and improving the reliability of the overall structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581331A_ABST
    Figure CN119581331A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a method for optimizing the roughness of the side wall of a glass through hole, which is used for solving the technical problem of high roughness of the side wall of the glass through hole manufactured by the existing glass through hole technology. According to the method, the femtosecond laser is adopted, and the material structure of the prefabricated through hole area is uniformly and deeply changed in a thermal cycle mode, so that the chemical etching sensitivity of the prefabricated through hole area is remarkably improved, and the prefabricated through hole area is more easily and uniformly removed; by optimizing the components and proportion of the etching liquid, the etching liquid uniformly covers and acts on the surface of the material in the modified area of the prefabricated through hole in the subsequent chemical etching stage, the modified material is corroded at a uniform speed, and corrosion residues are removed in time. Through etching liquid temperature control and ultrasonic power control, the mixing and reaction uniformity of the etching liquid is enhanced, and uniform and refined etching of the prefabricated through hole modification area is realized. And furthermore, the uniformity of glass through hole corrosion and the material removal precision are greatly improved, and the roughness of the side wall is obviously reduced from 1.257 microns to 100 nanometers or below.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of integrated circuit packaging, and in particular to a method for optimizing the roughness of a through-glass hole side wall. Background Art

[0002] Three-dimensional integrated packaging technology achieves high-density electrical interconnection by introducing vertical through-hole structures between multi-layer chips and components, and has become an important evolution direction of integrated circuit packaging technology. In this technology, the interposer, as an intermediary component connecting different chips and between chips and packaging substrates, plays an important role in meeting high-density I / O requirements. The ultra-thin glass interposer not only shortens the signal transmission path and effectively reduces latency, but also has excellent high-frequency electrical properties and low loss advantages, and has gradually become a core component in 2.5D and 3D packaging technology for high-frequency devices.

[0003] In the through glass via (TGV) technology, firstly, a modified area is formed on the glass substrate by pulses generated by a laser; then, these modified areas are removed by chemical etching to generate a through hole structure; finally, conductive metal materials are filled into these through holes by magnetron sputtering and electroplating processes to form a vertical interconnection structure. However, due to the non-uniformity of the chemical etching process, irregular pit-like structures often appear on the side walls of the through holes, making the RMS value of the side wall roughness usually exceed 1.257 microns, that is, the side walls of the through holes show the characteristics of high roughness.

[0004] Highly rough sidewalls can have many adverse effects on vertical interconnect structures consisting of through-holes. First, high-roughness sidewalls increase scattering and reflection effects during signal transmission, causing energy loss and reducing transmission efficiency, and may also generate electromagnetic interference. Second, the high roughness of the sidewalls makes the metallization and filling processes more complicated, affecting the bonding strength between the glass through-hole and the filling material, thereby reducing the overall reliability of the structure. In addition, the non-uniformity of the sidewall roughness may weaken the mechanical properties of the device under the action of thermal cycles or mechanical stress, and even cause the device to break or delaminate.

[0005] However, in the process of implementing the technical solutions in the embodiments of the present invention, the inventors found that the current through-glass via technology is still in the technical exploration stage, and there is no optimization solution for the roughness of the through-hole sidewalls. Summary of the invention

[0006] In view of this, an object of an embodiment of the present invention is to provide a method for optimizing the roughness of a through-glass via sidewall, so as to solve the technical problem of high roughness of the through-glass via sidewall manufactured by the existing through-glass via technology.

[0007] In order to achieve the above purpose, the technical solutions adopted in the embodiments of the present invention are as follows:

[0008] An embodiment of the present invention provides a method for optimizing the roughness of a through-glass hole sidewall, comprising the following steps:

[0009] Using a femtosecond laser, laser-induced modification of the prefabricated through-hole region is performed on the front and back sides of the glass substrate to form a prefabricated through-hole modified region;

[0010] Performing ultrasonic cleaning on the glass substrate that has been modified by laser induction to remove impurities and dirt on the surface;

[0011] preparing an etching solution consisting of deionized water, hydrofluoric acid, ammonium fluoride, isopropyl alcohol, and polyethylene glycol;

[0012] The cleaned glass substrate is placed in an etching tank of an ultrasonic etching device into which etching solution is pre-added, and the glass substrate is etched for 2.2 to 2.5 hours under the conditions that the etching solution temperature is 25° C. to 30° C. and the ultrasonic power is not less than 200W.

[0013] Optionally, the etching solution has the following components in volume ratio: 200 parts of deionized water, 32-41 parts of hydrofluoric acid, 22-30 parts of isopropanol, 6-10 parts of ammonium fluoride, and 3-6 parts of polyethylene glycol.

[0014] Optionally, the molecular weight of the polyethylene glycol is 900-3000.

[0015] Optionally, the molecular weight of the polyethylene glycol is 1000-1500.

[0016] Optionally, the steps of preparing an etching solution composed of deionized water, hydrofluoric acid, ammonium fluoride, isopropyl alcohol, and polyethylene glycol are specifically as follows:

[0017] Deionized water, hydrofluoric acid, isopropanol, ammonium fluoride and polyethylene glycol are gradually added into the preparation container in sequence according to the predetermined volume ratio of the components; each time a component is added, it is stirred evenly to ensure that a uniformly mixed etching solution is finally obtained.

[0018] Optionally, in the step of etching the glass substrate for 2.2 to 2.5 hours, the temperature of the etching solution is maintained at 25° C. to 30° C. specifically:

[0019] Deionized water is added to the water bath outside the etching tank. The liquid level of the deionized water is higher than the liquid level of the etching solution. The deionized water in the water bath is replaced every 10 to 15 minutes to control the temperature of the etching solution in the etching tank at 25°C-30°C.

[0020] Compared with the existing through-glass technology, the method for optimizing the roughness of the sidewall of the through-glass in the embodiment of the present invention adopts a femtosecond laser with ultrashort pulse time and high energy density to uniformly and deeply change the material structure of the prefabricated through-hole region in a thermal cycle, so that the sensitivity of the material in the modified region of the prefabricated through-hole to chemical etching is significantly improved, and it is easier to be uniformly and selectively removed; by optimizing the components and proportions of the etching solution, in the subsequent chemical etching stage, the etching solution uniformly covers and acts on the material surface of the modified region of the prefabricated through-hole, corrodes the modified material at a uniform speed and removes the corrosion residue in time. Through the control of the etching solution temperature and the control of the ultrasonic power, the cavitation effect and micro-jet effect of the ultrasonic wave are coordinated with the chemical etching to enhance the mixing and reaction uniformity of the etching solution, so as to achieve uniform and refined etching of the modified region of the prefabricated through-hole. In addition, the uniformity of the through-glass corrosion and the material removal accuracy are greatly improved, and the sidewall roughness is significantly reduced from 1.257 microns to below 100 nanometers. This low-roughness through-hole sidewall structure can significantly reduce the scattering and reflection effects in signal transmission, reduce energy loss, and improve transmission efficiency. At the same time, it enhances the bonding strength between the through-hole and the filling material, thereby improving the overall reliability of the structure.

[0021] Therefore, the method for optimizing the roughness of the sidewall of the through-glass via in the embodiment of the present invention not only significantly improves the hole-forming quality of the through-glass via, but also enhances the signal transmission performance of the glass substrate and the stability of the microelectronic packaging, laying a foundation for the widespread application of through-glass via technology in the micron- and nano-scale manufacturing fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 A schematic flow chart of a method for optimizing the roughness of a through-glass hole sidewall in an embodiment of the present invention is shown;

[0024] Figure 2 A microscopic photograph of a through-glass hole manufactured by the method for optimizing the sidewall roughness of a through-glass hole in an embodiment of the present invention is shown. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with practical applications and with reference to the drawings of the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] A glass substrate with a through-glass hole manufactured by a method for optimizing the roughness of a through-glass hole sidewall in an embodiment of the present invention is used for high-density interconnection in the field of electronic devices.

[0027] The TGO manufactured by the existing TGO technology has the technical problem of high sidewall roughness (RMS value usually exceeds 1.257 microns). Such TGO with high sidewall roughness will lead to the degradation of microelectronic packaging based on glass substrate, affecting the performance and stability of integrated circuits.

[0028] In the process of in-depth research on the existing through-glass via technology, the inventors found that the reason for the high roughness of the sidewalls of the through-glass vias is not simply due to the inability of the etching solution to effectively enter the through-glass via embedded in the glass substrate, but is closely related to the following factors: First, the prior art uses a picosecond laser to perform laser-induced modification on a glass substrate with high hardness and chemical stability to form a prefabricated through-hole modified area. However, due to the limitations of the picosecond laser, the structural change of the material in the modified area is small and the sensitivity to chemical etching is insufficient. Second, the composition of the existing etching solution is relatively simple, mainly designed for micropores and through-silicon vias, and the need to remove the corrosion residues inside the through-hole is not considered. Third, the existing ultrasonic chemical etching process is usually under the temperature conditions of 20°C to 50°C, the ultrasonic power is 10 to 50W, and the process parameters are set for through-silicon via etching, but the corrosion conditions of the through-glass vias are significantly different from those of the through-silicon vias, including the composition of the etching solution, the characteristics of the target material and the difficulty of processing.

[0029] The inventors found in the process of implementing the embodiments of the present invention that it depends on the sensitivity of the prefabricated through hole modified area material to chemical etching, the ability of the etching solution to uniformly etch the prefabricated through hole modified area material, and the uniformity of the chemical etching process. In view of these factors, the inventors explored one by one: if it is necessary to improve the sensitivity of the prefabricated through hole modified area material to chemical etching, it is necessary to start from controlling the laser induced modification; if it is necessary to improve the ability of the etching solution to uniformly etch the prefabricated through hole modified area material, it is necessary to start from optimizing the composition and ratio of the etching solution; if it is necessary to improve the uniformity of the chemical etching process, it is necessary to start from the etching solution temperature control and ultrasonic power control.

[0030] Based on the above understanding, the inventors provide a method for optimizing the roughness of the sidewall of a through-glass via, aiming to improve the hole-forming quality of the through-glass via, enhance the signal transmission performance of the glass substrate and the stability of the microelectronic package, and lay the foundation for the widespread application of through-glass via technology in the micron- and nano-scale manufacturing fields.

[0031] Figure 1 A schematic flow chart of a method for optimizing the roughness of a through-glass hole sidewall in an embodiment of the present invention is shown.

[0032] Now refer to Figure 1 As shown, an embodiment of the present invention provides a method for optimizing the roughness of a through-glass hole sidewall, comprising the following steps:

[0033] S110, using a femtosecond laser to perform laser-induced modification of the prefabricated through-hole region on the front and back sides of the glass substrate, respectively, to form a prefabricated through-hole modified region;

[0034] In the embodiment of the present invention, the laser used is a femtosecond laser. Compared with a picosecond laser, a femtosecond laser has an ultra-short pulse time and high energy density, which allows the surface of the material to be heated to a high temperature in an instant and then cooled rapidly, and the material structure of the prefabricated through-hole patterning area is uniformly and consistently modified in a thermal cycle manner, which significantly improves its sensitivity to chemical etching and makes it easier to be uniformly removed. At the same time, the use of a femtosecond laser for laser-induced modification can also accurately control the size of the pattern of the prefabricated through-hole modified area, making the pattern of the prefabricated through-hole modified area regular.

[0035] The specific implementation process of step S110 may be:

[0036] Adjust the working parameters of the femtosecond laser, including laser focal length, laser irradiation power, scanning speed, acceleration, etc.

[0037] For example, the working parameters of the femtosecond laser can be: laser focal length is 0.1-0.3 mm, laser irradiation power is 25-55% of the equipment power, scanning speed is 2-5 mm / s, acceleration is 10-50 mm / s 2 .

[0038] Placing the glass substrate with its front side facing upward on a stage of a laser device, and using a femtosecond laser to perform laser-induced modification on the prefabricated through-hole region on the front side of the glass substrate to form a prefabricated through-hole modified region on the front side;

[0039] The glass substrate is turned over and placed with the back side facing upward, and a femtosecond laser is used again to perform laser-induced modification on the prefabricated through-hole region on the back side of the glass substrate to form a prefabricated through-hole modified region on the back side;

[0040] Through step S110, the prefabricated through hole regions on the front and back sides of the glass substrate are uniformly and consistently deep modified using a femtosecond laser, and the material of the prefabricated through hole modified region formed has significantly improved sensitivity to chemical etching, making it easier to remove uniformly by chemical etching. At the same time, the deep modification causes a significant change in the material structure of the modified region and the non-modified region, which means that the boundary between the two is clear, which is conducive to the selective etching of the etching solution and forms a fine side wall surface.

[0041] S120, performing ultrasonic cleaning on the glass substrate that has been subjected to laser induced modification to remove impurities and dirt on the surface;

[0042] The specific implementation process of step S120 may be:

[0043] The glass substrate that has been modified by laser induction is immersed in a cleaning solution in a cleaning tank of an ultrasonic device, and the ultrasonic cleaning device is turned on to clean the glass substrate until impurities and dirt on the surface of the glass substrate are completely removed.

[0044] In the embodiment of the present invention, the cleaning solution may specifically be a mixed cleaning solution prepared by mixing deionized water, ethanol and an organic solvent in a certain proportion.

[0045] The glass substrate that has undergone laser induced modification is cleaned in step S120 to remove impurities and contaminants formed on the surface of the glass substrate during the laser modification process, especially impurities in the prefabricated through hole modification area, so that the chemical etching process is directly performed on the material at the interface of the prefabricated through hole modification area, which not only reduces the difficulty of chemical etching but also improves the uniformity of chemical etching.

[0046] S130, preparing an etching solution consisting of deionized water, hydrofluoric acid, ammonium fluoride, isopropyl alcohol, and polyethylene glycol;

[0047] In the embodiment of the present invention, the etching solution consists of deionized water, hydrofluoric acid, ammonium fluoride, isopropyl alcohol and polyethylene glycol.

[0048] in,

[0049] Deionized water, as a base liquid, is used to control the overall concentration of the etching solution.

[0050] Hydrofluoric acid is used to provide the main etchant component.

[0051] Ammonium fluoride, working synergistically with hydrofluoric acid, is used to enhance the etching effect of the etching solution and increase the etching rate.

[0052] Isopropyl alcohol is used to reduce the surface tension of the etching solution, inhibit the generation of bubbles, optimize the wettability of the etching solution to the prefabricated through-hole modified area, make the etching solution evenly cover and act on the prefabricated through-hole modified area, and ensure the uniformity of the etching process.

[0053] Polyethylene glycol: As a non-ionic surfactant, it is used to improve the uniform dispersion of the etchant and accelerate the removal of corrosion residues. At the same time, the non-hydrolysis, chemical inertness and thermal stability of polyethylene glycol ensure that it exhibits a long-lasting stabilizing effect during the formulation process.

[0054] In the embodiment of the present invention, in order to balance the solubility and viscosity of polyethylene glycol, ensure the formation of a uniform liquid film during the etching process, and promote the removal of corrosion residues, the molecular weight of the polyethylene glycol should be 900 to 3000. The polyethylene glycol with a molecular weight of 1000 to 1500 is a preferred polyethylene glycol due to its good solubility, low vapor pressure, and high surface activity.

[0055] The volume ratio of the components of the etching solution is: 200 parts of deionized water, 32-41 parts of hydrofluoric acid, 22-30 parts of isopropanol, 6-10 parts of ammonium fluoride, and 3-6 parts of polyethylene glycol. The etchant in the etching solution with this volume ratio is evenly dispersed, and has good wettability and penetration ability to the prefabricated through-hole modified area. In the subsequent etching process, it evenly covers and acts on the material surface of the prefabricated through-hole modified area, corrodes the modified material at a uniform speed, and removes the corrosion residues in the prefabricated through-hole in time.

[0056] The steps of preparing an etching solution composed of deionized water, hydrofluoric acid, ammonium fluoride, isopropyl alcohol, and polyethylene glycol are as follows:

[0057] Deionized water, hydrofluoric acid, isopropanol, ammonium fluoride and polyethylene glycol are gradually added into the preparation container in sequence according to the predetermined volume ratio of the components; each time a component is added, it is stirred evenly to ensure that a uniformly mixed etching solution is finally obtained.

[0058] The etching solution is configured according to a predetermined component volume ratio in step S130 to ensure that the etchant in the etching solution is evenly dispersed and can continuously and evenly remove and carry away material from the prefabricated through-hole modified area, thereby reducing local over-etching or uneven etching and improving the uniformity of glass through-hole etching.

[0059] S140, placing the cleaned glass substrate into an etching tank of an ultrasonic etching device into which the etching solution is pre-added, and performing etching treatment on the glass substrate for 2.2 to 2.5 hours under the conditions that the etching solution temperature is 25° C. to 30° C. and the ultrasonic power is not less than 200 W.

[0060] In the embodiment of the present invention, the hydrofluoric acid in the etching solution exhibits good etching uniformity and efficiency in the temperature range of 25° C. to 30° C., that is, 25° C.-30° C. is the optimal etching temperature range.

[0061] The specific steps of maintaining the temperature of the etching solution at 25°C to 30°C are as follows:

[0062] Deionized water is added to the water bath outside the etching tank. The liquid level of the ionized water is higher than the liquid level of the etching solution. The deionized water in the water bath is replaced every 10 to 15 minutes to control the temperature of the etching solution in the etching tank at 25°C-30°C.

[0063] The specific implementation process of step S140 may be:

[0064] Setting the working parameters of the ultrasonic etching equipment, wherein the ultrasonic power is not less than 200W;

[0065] The etching solution prepared in step S130 is pre-added into the etching tank of the ultrasonic etching equipment, and the temperature thereof is maintained at 25° C. to 30° C.;

[0066] Immersing the cleaned glass substrate into the etching solution in the etching tank, so that the material in the modified area of ​​the prefabricated through hole that is uniformly and deeply modified is wetted and uniformly covered by the etching solution;

[0067] The ultrasonic etching equipment is turned on, and the cavitation effect and micro-jet effect of ultrasound are used in conjunction with chemical etching to enhance the mixing and reaction uniformity of the etching solution. The etching solution acts evenly on the material in the modified area of ​​the prefabricated through hole and removes it at a uniform speed. The corrosion residue is promptly removed by the polyethylene glycol in the etching solution. Finally, after 2.2 to 2.5 hours of etching, a high-quality glass through hole is formed on the glass substrate.

[0068] Figure 2 A microscopic photograph of a through-glass hole manufactured by the method for optimizing the sidewall roughness of a through-glass hole in an embodiment of the present invention is shown.

[0069] Now refer to Figure 2 As shown in the micrograph, the radial dimension of the through-glass hole is well controlled, and the RMS value of the through-glass hole sidewall roughness is controlled below 100 nanometers.

[0070] In step S140, an etching solution with uniform material removal capability is used to etch the prefabricated through-hole modified area of ​​the glass substrate that is uniformly, consistently and deeply modified in a uniform and highly active etching environment to form a through-glass hole in a continuous, uniform and high-precision material removal manner. The through-glass hole has high surface quality and its side wall roughness is as low as less than 100 nanometers.

[0071] The method for optimizing the roughness of the sidewall of the glass through hole in the embodiment of the present invention improves the sensitivity of chemical etching of the material in the modified area of ​​the prefabricated through hole by precisely controlling the laser-induced modification, optimizes the composition and ratio of the etching solution, improves the uniform dispersion of the etchant in the etching solution and the ability of the etching solution to uniformly cover and act on the material surface of the modified area of ​​the prefabricated through hole, optimizes the synergistic effect of the chemical etching conditions, improves the uniformity of the chemical etching process, and realizes uniform and refined etching of the modified area of ​​the prefabricated through hole.

[0072] In the laser-induced modification stage, the femtosecond laser, with its ultrashort pulse time and high energy density characteristics, accurately irradiates the prefabricated through-hole areas on the front and back of the glass substrate, forming local instantaneous high temperatures on the surface of the glass material, followed by rapid cooling, and uniformly and deeply changing the material structure of the prefabricated through-hole area in a thermal cycle, significantly improving its sensitivity to chemical etching and making it easier to remove evenly. This helps to reduce the unevenness of subsequent etching and improve the quality of through-hole formation. At the same time, the use of femtosecond lasers to perform laser-induced modification on the prefabricated through-hole areas on the front and back of the glass substrate can also accurately control the graphic size of the prefabricated through-hole modification area.

[0073] Before chemical etching, an etching solution composed of deionized water, hydrofluoric acid, ammonium fluoride, isopropyl alcohol and polyethylene glycol is prepared. In the etching solution, hydrofluoric acid is used as the main etchant, ammonium fluoride is used to enhance the etching effect and optimize the corrosion rate, isopropyl alcohol is used to reduce the surface tension of the etching solution, improve the penetration ability of the etching solution to the modified area, and inhibit the generation of bubbles; polyethylene glycol is used as a surfactant to improve the uniform dispersion of the etching agent and accelerate the removal of corrosion residues. In the subsequent etching process, the etching solution uniformly covers and acts on the material surface of the prefabricated through-hole modified area, corrodes the modified material at a uniform speed, and avoids local over-corrosion or uneven corrosion.

[0074] During the chemical etching stage, the temperature of the etching solution is controlled within the optimal etching temperature range of 25°C-30°C to improve the uniformity and efficiency of the etching, and an ultrasonic power of not less than 200W is used to utilize the ultrasonic cavitation effect and micro-jet action in coordination with chemical etching to enhance the mixing and reaction uniformity of the etching solution, thereby achieving uniform and refined etching of the prefabricated through-hole modified area. During the etching process, the etching solution uniformly covers and acts on the material surface of the prefabricated through-hole modified area, corrodes the modified material at a uniform rate, and removes the corrosion residue in a timely manner. Ultimately, the surface quality of the inner wall of the glass through-hole formed by etching is significantly improved, and the side wall roughness is reduced to below 100 nanometers.

[0075] Through this working mechanism, the method for optimizing the roughness of the through-glass hole sidewall in the embodiment of the present invention significantly reduces the roughness of the through-glass hole sidewall from 1.257 microns to less than 100 nanometers, effectively solving the technical problem of high roughness of the through-glass hole sidewall manufactured by the existing through-glass hole technology. This method improves the application prospects of glass substrates in the field of three-dimensional integrated packaging technology.

[0076] Compared with the existing through-glass technology, the method for optimizing the roughness of the sidewall of the through-glass in the embodiment of the present invention adopts a femtosecond laser with ultrashort pulse time and high energy density to uniformly and deeply change the material structure of the prefabricated through-hole region in a thermal cycle, so that the sensitivity of the material in the modified region of the prefabricated through-hole to chemical etching is significantly improved, and it is easier to be uniformly and selectively removed; by optimizing the components and proportions of the etching solution, in the subsequent chemical etching stage, the etching solution uniformly covers and acts on the material surface of the modified region of the prefabricated through-hole, corrodes the modified material at a uniform speed and removes the corrosion residue in time. Through the temperature control of the etching solution and the ultrasonic power control, the cavitation effect and micro-jet effect of the ultrasonic wave are coordinated with the chemical etching to enhance the mixing and reaction uniformity of the etching solution, so as to achieve uniform and refined etching of the modified region of the prefabricated through-hole. In addition, the uniformity of the through-glass corrosion and the material removal accuracy are greatly improved, and the sidewall roughness is significantly reduced from 1.257 microns to below 100 nanometers. This low-roughness through-hole sidewall structure can significantly reduce the scattering and reflection effects in signal transmission, reduce energy loss, and improve transmission efficiency. At the same time, it enhances the bonding strength between the through-hole and the filling material, thereby improving the overall reliability of the structure.

[0077] Therefore, the method for optimizing the roughness of the sidewall of the through-glass via in the embodiment of the present invention not only significantly improves the hole-forming quality of the through-glass via, but also enhances the signal transmission performance of the glass substrate and the stability of the microelectronic packaging, laying a foundation for the widespread application of through-glass via technology in the micron- and nano-scale manufacturing fields.

Claims

1. A method for optimizing the roughness of a through-glass hole sidewall, characterized in that: The following steps are involved: Using a femtosecond laser, laser-induced modification of the prefabricated through-hole region is performed on the front and back sides of the glass substrate to form a prefabricated through-hole modified region; Performing ultrasonic cleaning on the glass substrate that has been modified by laser induction to remove impurities and dirt on the surface; preparing an etching solution consisting of deionized water, hydrofluoric acid, ammonium fluoride, isopropyl alcohol, and polyethylene glycol; The cleaned glass substrate is placed in an etching tank of an ultrasonic etching device into which etching solution is pre-added, and the glass substrate is etched for 2.2 to 2.5 hours under the conditions that the etching solution temperature is 25° C. to 30° C. and the ultrasonic power is not less than 200W.

2. The method for optimizing the sidewall roughness of a through-glass hole according to claim 1, characterized in that: The volume ratio of the components of the etching solution is: 200 parts of deionized water, 32-41 parts of hydrofluoric acid, 22-30 parts of isopropanol, 6-10 parts of ammonium fluoride, and 3-6 parts of polyethylene glycol.

3. The method for optimizing the sidewall roughness of a through-glass hole according to claim 2, characterized in that: The molecular weight of the polyethylene glycol is 900-3000.

4. The method for optimizing the sidewall roughness of a through-glass hole according to claim 3, characterized in that: The molecular weight of the polyethylene glycol is 1000-1500.

5. The method for optimizing the sidewall roughness of a through-glass hole according to any one of claims 1 to 4, characterized in that: The steps of preparing an etching solution composed of deionized water, hydrofluoric acid, ammonium fluoride, isopropyl alcohol, and polyethylene glycol are as follows: Deionized water, hydrofluoric acid, isopropanol, ammonium fluoride and polyethylene glycol are gradually added into the preparation container in sequence according to the predetermined volume ratio of the components; each time a component is added, it is stirred evenly to ensure that a uniformly mixed etching solution is finally obtained.

6. The method for optimizing the sidewall roughness of a through-glass hole according to any one of claims 1 to 4, characterized in that: The specific steps of maintaining the temperature of the etching solution at 25° C. to 30° C. during the step of etching the glass substrate for 2.2 to 2.5 hours are as follows: Deionized water is added to the water bath outside the etching tank. The liquid level of the deionized water is higher than the liquid level of the etching solution. The deionized water in the water bath is replaced every 10 to 15 minutes to control the temperature of the etching solution in the etching tank at 25°C-30°C.

Citation Information

Cited By

  • Glass etching device for laser induction and fluoride-free etching method

    CN120208520A